The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jdv.18344
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive, in vivo, characterization of cutaneous metastases using a novel multimodal RCM‐OCT imaging device: a case‐series

Abstract: Background Cutaneous metastases (CM) diagnosis is clinically challenging, requiring an invasive biopsy for confirmation. A novel, RCM‐OCT device combines the advantage of horizontal high‐resolution reflectance confocal microscopy (RCM) images and vertical deeper optical coherence tomography (OCT) images to aid in non‐invasive diagnosis of CM from breast cancers. Objective Characterize CM from breast cancers using RCM‐OCT device. Methods Seven patients suffering from breast cancers with suspicious CM were conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Farnetani et al showed that RCM can be used for the immediate diagnosis of melanoma metastases, 1 the described criteria were also visible in LC-OCT in the present study (Table 1). 1,2 Bang et al reported in a small case series signs of metastases of breast cancer in a RCM-OCT device. 2 Hyporeflective areas with clusters of hyporeflective cells surrounded by bundles of collagen fibres and inflammatory cells seem to be common findings of CM regardless of tumour entity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Farnetani et al showed that RCM can be used for the immediate diagnosis of melanoma metastases, 1 the described criteria were also visible in LC-OCT in the present study (Table 1). 1,2 Bang et al reported in a small case series signs of metastases of breast cancer in a RCM-OCT device. 2 Hyporeflective areas with clusters of hyporeflective cells surrounded by bundles of collagen fibres and inflammatory cells seem to be common findings of CM regardless of tumour entity.…”
Section: Discussionmentioning
confidence: 99%
“… 1,2 Bang et al reported in a small case series signs of metastases of breast cancer in a RCM–OCT device 2 . Hyporeflective areas with clusters of hyporeflective cells surrounded by bundles of collagen fibres and inflammatory cells seem to be common findings of CM regardless of tumour entity 1,2 . However, the visualization of pagetoid and dendritic cells in LC‐OCT might enable the immediate diagnosis of melanoma metastases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations